Using visual demonstrations in young adults to promote smoking cessation: Preliminary findings from a French pilot study - Burford, Oksana; Kindarji, S.; Parsons, R.; Falcoff, H. (Elsevier, 2017)
Background: A personalised, smoking cessation message was successfully delivered in Australian community pharmacies to motivate behavioural change in young smoking adults. Objective: The purpose of this pilot study was to test the acceptability and effectiveness of the innovative, proven smoking cessation intervention to another population of young adults with a higher prevalence of smoking and associated morbidities. Methods: Ninety eight university students in Paris, France were recruited to a pilot study (50 intervention: 48 control). All students received smoking cessation counselling sessions and half also received a visual demonstration of themselves, both as a lifelong smoker and non-smoker. Results: There was no statistical significant difference between the groups in smoking dependence at recruitment. At the three month follow-up, the proportion who had attempted to quit smoking were 37% (control) vs 46% (intervention). These percentages suggested a positive result for the intervention, although the difference was not statistically significant (p = 0.39). Conclusion: This is one of the first studies conducted in France using visual demonstrations combined with healthcare counselling to promote smoking cessation amongst young adult smokers. Further research, recruiting from the general French public, is needed to better understand if the innovative personalised health message can motivate young French adult smokers to quit.